Odpowiedzi

2010-02-24T13:08:26+01:00

a) (-3) * 0,2 =-0,6
b) 6 * ( - ⅓ )=-2
c) (-1,3) * (-2) =2,6
d) (-9) * ( - ½ ) =4i1/2
e) (- ²/₇) * ⁷/₁₂) =-1/6
f) (-12) : 6 =-2
g) (-4) : (-8) =0,5
h) 3,2 : (-2) =-1,6
i) ( -¾) : ¼ =-3
j) (-0,1)² =0,01
k) (-2)³ =-8
l) (-½)⁴= 1/16
Najlepsza Odpowiedź!
2010-02-24T13:09:24+01:00
A) (-3) * 0,2 = -0,6
b) 6 * ( - ⅓) = -6/3 = -2
c) (-1,3) * (-2) = 2,6
d) (-9) * ( - ½ ) = 9/2 = 4,5
e) (- ²/₇) * ⁷/₁₂) = -14/84 = -1/6
f) (-12) : 6 = -2
g) (-4) : (-8) = 0,5
h) 3,2 : (-2) = -1,6
i) ( -¾) : ¼ = -12/4 = -3
j) (-0,1)² = 0,01
k) (-2)³ = -8
l) (-½)⁴= 1/16
1 5 1
2010-02-24T13:12:33+01:00
A) -0,6
b)-2
c)2,6
d)4,5
e)-2/II
f)-2
g)0,5
h)-1,6
i)-3
j)0,01
k)-8
l)-I1/2